2007
DOI: 10.1186/1749-7922-2-22
|View full text |Cite
|
Sign up to set email alerts
|

Dying from cardiac tamponade

Abstract: Background: To determine the causes of cardiac tamponade (CT), focussing especially on haemopericardium (HP), as a terminal mode of death, within a 430,000 rural English population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…Spontaneous hemopericardium unrelated to trauma is known to occur in 2.5–11% of patients receiving any anticoagulation . Rapidly evolving hemopericardium (200–300 ml) can cause death from cardiac tamponade compared with large but slow accumulation (500–2000 ml), as increased intrapericardial pressure decreases diastolic filling with subsequent hypotension …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spontaneous hemopericardium unrelated to trauma is known to occur in 2.5–11% of patients receiving any anticoagulation . Rapidly evolving hemopericardium (200–300 ml) can cause death from cardiac tamponade compared with large but slow accumulation (500–2000 ml), as increased intrapericardial pressure decreases diastolic filling with subsequent hypotension …”
Section: Discussionmentioning
confidence: 99%
“…3 Rapidly evolving hemopericardium (200-300 ml) can cause death from cardiac tamponade compared with large but slow accumulation (500-2000 ml), as increased intrapericardial pressure PHARMACOTHERAPY Volume 34, Number 9, 2014 decreases diastolic filling with subsequent hypotension. 4,5 Rivaroxaban is an orally bioavailable FXa inhibitor. 2 Activation of FX to FXa through the intrinsic and extrinsic clotting pathways plays a central role in the cascade of coagulation.…”
Section: Discussionmentioning
confidence: 99%
“…While in the 1960s its most common aetiology was dissecting aortic or syphilitic aneurysms, in a series published by Atar et al 14 in 1999, iatrogenic trauma, malignancy and myocardial infarction were found to be the foremost aetiologies. In another series published by Swaminathan et al 15 in 2007, myocardial infarction and dissecting aortic aneurysm were the top causes. Others have also identified blunt chest trauma as an aetiology 16…”
Section: Discussionmentioning
confidence: 99%
“…However, the possibility of myocardium invasion via hematogenous dissemination also may occur. 6,8 The etiology of myocardial rupture is most commonly a result of myocardial infarction, 9 with much less common causes being cardiac trauma, endocarditis, primary and secondary cardiac tumors, infiltrative diseases of the heart, and aortic dissection. [10][11][12] The presentation of cardiac tumors is variable.…”
Section: Discussionmentioning
confidence: 99%